Drilling CF/PEEK thermoplastic composite: Optimization of drill point angle and cutting parameters using nature-inspired hybrid optimization - Tosun, Onur; Aydin, Mevlut; Yapan, Yusuf Furkan; Uysal, Alper (ELSEVIER SCI LTD, 2026)
Developing reliable and sustainable machining strategies for CF/PEEK composites has become an urgent necessity due to the growing demand for recyclable high-performance materials in aerospace applications and the persistent lack of drilling knowledge tailored to their thermally sensitive and damage-prone nature. In this context, the focus of this study is the drilling performance of CF/PEEK thermoplastic composites. Addressing a current research gap, this study examined specific drill point angles in dry drilling CF/PEEK for the first time. The input parameters considered are the drill point angles (DPAs) of 80 degrees, 80/120 degrees and 120 degrees, which have not been examined before, as well as the spindle speed (S) of 1000, 1500 and 2000 rpm and the feed rate (f) of 100, 200 and 300 mm/min. Drilling performance was evaluated regarding thrust force (Ft), cutting temperature (Tc), surface roughness (Ra), hole quality, and roundness error (RE). Using a 120 degrees DPA and under appropriate process conditions, improvements of up to 81.1%, 57.2%, 69.2%, and 75.8% were achieved for Ft, Tc, Ra, and RE, respectively. Furthermore, the optimal drilling condition was determined through the integration of the Multi-Objective Water Cycle Algorithm (MOWCA) and the Entropy-based MARCOS multi-criteria decision-making approach. Based on the ranking results, the best process parameter combination was identified as a DPA of 120 degrees, S of 2000 rpm, and f of 100 mm/min. Under these optimal conditions, the optimized output parameters were obtained as 306.79 N for Ft, 177.18 degrees C for Tc, 0.4655 mu m for Ra, and 0.3264 mm for RE. These findings provide practical machining guidelines for overcoming the challenges of dry drilling CF/PEEK thermoplastic composites, thereby supporting their reliable integration into the aerospace manufacturing process.
Keywords: CF/PEEK; Thermoplastic composite; Drilling; Drill point angle; Multi-objective optimization; WATER CYCLE ALGORITHM; UD-CF/PEEK; SURFACE; FORCE; DRY; MACHINABILITY; MODEL; Engineering; Materials Science